CHARACTERISTICS OF CLINICAL- MORPHOMETRIC PARAMETERS AND EVALUATION OF RESULTS OF SURGICAL TREATMENT OF PATIENTS WITH GNATHIC FORMS OF OCCLUSION ANOMALIES - Dusmukhamedov, Dilshod M. (International Journal of Psychosocial Rehabilitation, 2020)
Some authors’ analyses indicated that the search for the best treatment option for patients with congenital and acquired facial skeleton deformations has been going on for more than 40 years and it does not disappear significance even today. The aim wasto study the clinical and morphometric parameters of patients with gnathic forms of occlusion anomalies and to evaluate results of surgical treatment. Archival materials of 38 patients who were under medical observation at the Department of Pediatric Maxillofacial Surgery at the Tashkent State Dental Institute Clinic were analyzed for evaluating morphometric parameters of maxillofacial part of patients with congenital and acquired facial skeleton deformations. Classification of malocclusion which proposed by E. Angle were used in order to identify deformity of the facial skeleton, depending on the severity in one plane or another, type of affiliation. Based on the analysis of the research results, the treatment and rehabilitation of patients with common deformities of the jaw, and patients with congenital and acquired facial skeleton deformations in particular, cause great difficulties and require additional procedures to organize their psychological rehabilitation.